The Existence of Blind Radio Drama Represents the Real World - Adnan, Muhammad; Tantri, Niki Raga; Pribadi, Fantri; Astari, Andi Tenri Juli; Utama, Galuh Tulus (Titian: Jurnal Ilmu Humaniora, 2025)
Radio drama, as an auditory medium, is often perceived as "blind" due to its lack of visual modality, making its representation of reality a unique challenge. This qualitative research, employing a semiotic analysis approach, aims to analyze the forms of denotative and connotative messages in radio drama and examine its strategies for conveying a story that listeners can understand. Data were collected through literature study and in-depth interviews with listeners, then analyzed interactively. The results indicate that radio drama constructs understanding through audio symbols, such as dialogue, sound effects, and music, which listeners recognize based on prior sensory experiences. These symbols convey not only literal meaning (denotative) but also evoke emotional and cultural values (connotative). Therefore, although "blind," radio drama richly represents the real world through the power of sound and the listener's active imagination, proving that the absence of visuals is not a limitation but a unique characteristic that enables the creation of its own reality. Abstract Drama radio, sebagai medium auditif, sering dianggap “buta” karena tidak menyertakan modalitas visual, sehingga representasi realitasnya menjadi tantangan tersendiri. Penelitian kualitatif dengan pendekatan analisis semiotika ini bertujuan untuk menganalisis bentuk pesan denotatif dan konotatif dalam drama radio serta mengkaji strateginya dalam menyampaikan cerita yang dapat dipahami pendengar. Data dikumpulkan melalui studi literatur dan wawancara mendalam dengan pendengar, kemudian dianalisis secara interaktif. Hasil penelitian menunjukkan bahwa drama radio membangun pemahaman melalui simbol-simbol audio, seperti dialog, efek suara, dan musik, yang dikenali pendengar berdasarkan pengalaman inderawi sebelumnya. Simbol-simbol ini tidak hanya menyampaikan makna harfiah (denotatif) tetapi juga membangkitkan nilai emosional dan kultural (konotatif). Dengan demikian, meskipun “buta,” drama radio justru merepresentasikan dunia nyata secara kaya melalui kekuatan suara dan imajinasi aktif pendengar, membuktikan bahwa ketiadaan visual bukanlah bentuk keterbatasan, melainkan keunikan yang memungkinkan terciptanya realitas tersendiri.